Nuovi studi su Kyme eolica: produzioni e rotte trasmarine New studies on Aeolian Kyme: productions and transmarine routes - Lucia A. Scatozza Höricht (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2012)
The volume includes a series of contributions related to the handicraft productions of the ancient city of Aeolian Kyme (Turkey), edited with the purpose of investigating, through their circulation, the relations of the Aeolian metropolis with other areas of the Aegean see and of the ancient Mediterranean. The work deals with a difficult field of investigation, as not all the Anatolian manufacturing centres, including Kyme, have been properly documented so far. Researches carried out by archaeologists of the University of Naples, University of Calabria and University of Milan, who participate in the activities of the Italian Archaeological Mission in Kyme, reveal the economic role that the city of Kyme had in various historical period. It was a seaport of primary importance, located at the mouth of the Ermo river, which was the main transport route to the Anatolian inland, along the north-south costal road.